Domestic Violence Law and Maqāṣid al-Syarī’ah in Protecting Families from Psychological Violence - Iffaty Nasyi’ah; Muhammad Nasrulloh; Zummy Humairoh; Fakhruddin Fakhruddin; Rafeah Saidon (Universitas Negeri Semarang, 2026)
This study aims to reconstruct protection against psychological violence under Article 7 of the Domestic Violence Eradication Law through the perspective of Maqāṣid al-Syarī‘ah to strengthen legal certainty and improve victim protection. The study is motivated by the vague indicators of psychological violence, which weaken evidentiary standards and create inconsistent law enforcement. This research employs normative legal research using statutory and conceptual approaches analyzed descriptively and analytically. The findings show that psychological violence produces multidimensional impacts on the objectives of Maqāṣid al-Syarī‘ah. At the level of ḍarūriyyāt, it harms life through mental disorders, weakens intellect through cognitive distortion, disrupts religion through spiritual crises, damages lineage through psychological trauma, and reduces economic stability. At the level of ḥājiyyāt, it causes emotional distress and impairs social functioning, while at the level of taḥsīniyyāt, it degrades ethics, morality, and family relationships. Conversely, stronger psychological protection supports mental stability, religious observance, intellectual functioning, generational resilience, economic productivity, and harmonious family relations. This study confirms that the integration of Article 7 of the Domestic Violence Law with Maqāṣid al-Syarī‘ah strengthens psychological protection through preventive, repressive, and restorative approaches oriented toward public welfare and the protection of human dignity. The novelty of this research lies in integrating positive legal norms with Maqāṣid al-Syarī‘ah to formulate a comprehensive psychological protection model.